Hydatidosis: A rare case of bilateral tubo ovarian Hydatid cyst - N.Sharifi (M.D); K.Ghafarzadegan (M.D) (مجله دانشگاه علوم پزشکی گرگان, 2002)
Hydatidosis is a parasitic infection mostly in found in the liver and lung due to echinococus species. But occurrence in other locations is possible. Purpose of this report is to describe a case of bilateral Hydatid cyst in ovaries. Clinical findings with this uncommon location are poorly specific and diagnosis required histologic examination after surgical removal. Imaging and serology is useful to differentiate Hydatid cyst from benign and malignant tumors. This obligatory to examine lung and liver as the main sites of cyst when you are being faced with unusual location of Hydatid cyst especially in endemic area such as Iran. Our patients was a 35 years old woman with history of 4-month abdominal pain in left and right lower quadran. Sonography showed two cysts in adenexal lesions after surgical removal, they were sent to pathology lab. Hydatic cyst membrane was seen in histologic examination of two cystic masses.